STATUS HALAL PRODUK FROZEN FOOD TOKO OM JACK DI KOTA PONTIANAK MENURUT UNDANG-UNDANG NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL - Permana, Habibillah Putra; Ardiansyah, Ardiansyah; Suhardiman, Suhardiman (Al-Aqad, 2025)
This research is motivated by the continued circulation of frozen food products that do not have halal certification, even though clarity of halal status is a Muslim consumer right and has been regulated in Law Number 33 of 2014 concerning Halal Product Guarantee. This study aims to determine the practice of selling frozen food products that do not have halal certification at Om Jack Store in Pontianak City and analyze the halal status of these products based on the provisions of the Halal Product Guarantee Law. The type of research used is empirical juridical research with a qualitative approach. Data were obtained through interviews, observations, and documentation, then analyzed using qualitative descriptive data analysis techniques by means of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the practice of selling frozen food products at Om Jack Store is carried out as is the practice of trade in general, but some of the products traded do not have halal certification. Based on Article 4 of Law Number 33 of 2014, products circulating and traded in the territory of Indonesia are in principle required to be halal certified, so the practice of selling frozen food products without halal certification is not fully in accordance with applicable legal provisions. Therefore, it is necessary to increase supervision and awareness of business actors regarding the importance of halal product guarantees as a form of legal protection for consumers, especially Muslims.